Acrokeratosis verruciformis of Hopf - Case report - Tatiana Cristina Pedro Cordeiro de Andrade; Gardênia Viana da Silva; Tatiane Meira Pinho Silva; Ana Cecília Versiani Duarte Pinto; Adauto José Ferreira Nunes; Antônio Carlos Ceribelli Martelli (Sociedade Brasileira de Dermatologia, 2016)
Abstract: A 54 year-old woman with a 3-year history of rheumatoid arthritis (RA) consulted us because of weight loss, fever and skin eruption. On physical examination, erythematous plaques with a pseudo-vesicular appearance were seen on the back of both shoulders. Histological examination was consistent with rheumatoid neutrophilic dermatosis (RND). After three days of prednisone treatment, the skin eruption resolved. RND is a rare cutaneous manifestation of seropositive RA, characterized by asymptomatic, symmetrical erythematous plaques with a pseudo-vesicular appearance. Histology characteristically reveals a dense, neutrophilic infiltrate with leucocitoclasis but without other signs of vasculitis. Lesions may resolve spontaneously or with RA treatment. This case illustrates an uncommon skin manifestation of active rheumatoid arthritis.